أحكام الأسرة وأثرها في تحفيز الصحة النفسية للأفراد: Family Provisions And Their Impact On Stimulating The Mental Health Of Individuals - Saad Allafi, Mathayel Mubark (Al-Basirah Journal, 2023)
Because there is a dearth of research that studies the effect of family judgments on activating the mental health of individuals, the researcher did this study and made the following main objectives: recognizing the concept of mental health from an Islamic perspective, with an indication of the importance of mental health for family members, knowing the factors of mental health, and clarify the treatments established by Islamic judgments to support the mental health of men, women and children. The study concluded with several results, the most important of which are: the factors on which mental health depends are numerous, the most important of which are: the balance of personality, controlling impulses, cultivating needs, controlling emotions, achieving self-conformity. The family rulings in Islamic jurisprudence have a direct role in supporting psychological and mental health, and the Islamic concept of mental health fulfills the four aspects of health, spiritual, psychological, social and physical (biological).